2018
DOI: 10.4314/jsdlp.v9i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Turning fish soup back into fish: The wicked problem of African Community land rights

Abstract: Africa's postcolonial disputes over community land rights are a "wicked" problem, not evil, but resistant to resolution. This article investigates three such disputes in Kenya (Endorois, Ogiek and Nubian community) where the African Commission and Court of Human and Peoples' Rights have determined in the communities' favour but the implementation is not progressing, both because of opposition by the state and the complex and long-standing nature of the cases. The legal history of colonial trust lands and recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In turn, Bennett et al (2017, p. 59) argue that “[s]ocio-economic inequalities such as poverty still remain a challenge in post-apartheid South Africa and continue to impact the country by contributing to the burden of disease and social health faced by the population,” with the poorest potentially being the worst affected. Furthermore, Chasi (2017, p. 497) discusses Nelson Mandela’s efforts to communicate the HIV/AIDS problem and claims that the president was forced to work in a post-apartheid situation where leadership was difficult and “in societal arrangements that quite intractably constrain what they [leaders] can do to secure a more just social order.” Other problems in this group include the long-term effects of colonial (and post-colonial) rule on indigenous peoples and ethnic groups (Home & Kabata, 2018), and more general social and ecological issues in South African post-apartheid society (Mertens, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In turn, Bennett et al (2017, p. 59) argue that “[s]ocio-economic inequalities such as poverty still remain a challenge in post-apartheid South Africa and continue to impact the country by contributing to the burden of disease and social health faced by the population,” with the poorest potentially being the worst affected. Furthermore, Chasi (2017, p. 497) discusses Nelson Mandela’s efforts to communicate the HIV/AIDS problem and claims that the president was forced to work in a post-apartheid situation where leadership was difficult and “in societal arrangements that quite intractably constrain what they [leaders] can do to secure a more just social order.” Other problems in this group include the long-term effects of colonial (and post-colonial) rule on indigenous peoples and ethnic groups (Home & Kabata, 2018), and more general social and ecological issues in South African post-apartheid society (Mertens, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The wicked problems in Africa reviewed in the present study are, for their part, highly context-specific and politically, culturally, and historically intertwined. For example, Home and Kabata (2018, p. 3) describe the case of “descendants of Nubian soldiery that served the British colonial power” living in Kenya. Nubian soldiers were recruited by the British at the beginning of the 20th century and remained in Kenya after their service.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The charter, signed in a time of decolonization, frequently refers to the rights of 'peoples' (in the plural) to development, and to hold natural resources and property, but this commitment has been complicated by the UN Declaration on the Rights of Indigenous Peoples (2007). In three key cases affecting Kenya-two of them brought by indigenous peoples, the third by Nubian descendants of the colonial military-the African Court found for the appellants multiple breaches of their charter rights [72,73]. The Mbiankeu case confirmed that a valid land certificate was proof of property ownership guaranteed by the state, and required the Cameroonian government to annul a fraudulent title and compensate the victim.…”
Section: Supranational Regional and Human Rights Actorsmentioning
confidence: 99%